Media markets and competition law multinational perspectives - Evans, David S. 1954- (Competition Policy International, 2019)
This book is a selection of 14 brief essays designed to provide a multinational perspective on the current state, and future, of competition law in media markets. Whether it pertains to platform markets, crypto-currencies, or newspaper mergers, the reality is that antitrust enforcement has turned its collective eye towards the global economy's media markets. It highlights the different regulatory approaches and various issues relating to the application of competition law to media markets
Keywords: Competition, Unfair; Commercial law; Antitrust law; International law; Mass media / Law and legislation; LAW / Antitrust; LAW / International; LAW / Media & the Law